Retrospective Analysis of the Clinical Characteristics of Candida auris Infection Worldwide From 2009 to 2020 - Hu, Shan; Zhu, Feilong; Jiang, Weiwei; Wang, Yuehua; Quan, Yongqiang; Zhang, Guoming; Gu, Feng; Yang, Ying (Frontiers in Microbiology, 2021)
Introduction: Candida auris is an emerging multidrug-resistant fungus that may cause infections with a high mortality rate. The first case of C. auris infection was reported in 2009 and infections have been reported in 44 countries. The fungus now represents a major global public health threat. We analyzed cases from the emergence of C. auris infections up until the end of 2020. It is hoped that the results of this analysis will raise awareness in scientists to promote protection and control research pertaining to this pathogen. Methods: PubMed and Web of Science databases were searched for all papers related to C. auris infections up until December 31, 2020. We sorted and organized these data into the following categories: date of publication, patient age and sex, underlying diseases, risk factors for infection, patient mortality information, drug sensitivity information of C. auris isolates, and genetic classification. The χ2 test was used to screen for factors that may affect patient mortality. If there were multiple indicators that were significant at P<0.05, we used logistic regression for multivariate analysis; otherwise, we did not perform multivariate analysis. Results: A total of 912 patients were included in the analysis. The male to female ratio was more than 3:2 and a high proportion of patients were premature babies and elderly people. The proportions of patients with underlying diseases such as diabetes, kidney disease, trauma, and ear disease were also high. A total of 55.1% of patients had a history of central venous catheter use and 55.9% of patients were given broad-spectrum antibiotics. The χ2 test revealed that only kidney disease (P<0.05) was an important risk factor for mortality in C. auris-infected patients. In addition, almost all patients infected with echinocandin-resistant C. auris ultimately died. Conclusions: A comprehensive understanding of C. auris was achieved following this retrospective analysis, including the characteristics of C. auris-infected patients, and in particular characteristics associated with deaths caused by C. auris. In recent years, increasing numbers of multidrug-resistant C. auris isolates have been identified, and the high mortality rates associated with infection merit greater attention from the medical world.